The Future of Luther's Theology - Hendrix, Scott H. (Dialog, 2008)
Some historical observations need to be made about Luther in his own time before his thought can be made useful for our future. First, theology was a collaborative undertaking for Luther and his Wittenberg colleagues. Second, theology was tied to their Reformation agenda of teaching a new way of practicing Christianity in accord with the gospel. That agenda required radical changes: a conversion of religious efforts to please God into advocacy of the neighbor; expansion of the church beyond Rome into an ecumenical assembly of holy and active believers; and a theological reorganization of public life that blurred the line between theology and ethics. In these areas, adapted to the 21st century, lies the greatest utility of Luther's theology for the future.